Participatory process for developing system dynamics models to guide interventions in the context of agri-food and livestock value chains - CGIAR Research Program on Livestock (2019)
The innovation has to date been tested in Nicaragua, Zambia, Myanmar, India, Bangladesh and Vietnam and is available for use in any country.